Non-additive effects of litter mixtures on decomposition of leaf litters in a Mediterranean maquis (Plant and Soil, 2011)
Many studies across a range of ecosystems have shown that decomposition in mixed litter is not predictable from single-species results due to synergistic or antagonistic interactions. Some studies also reveal that species composition and relative abundance may be more important than just richness in driving non-additive effects. Most studies on litter decomposition in Mediterranean maquis, an highdiversity shrubby ecosystem, have dealt exclusively with single species. In this study we investigated, at the individual-litter level, as well as at the littermixture level, the effect of litter mixing on decomposition of 3-species litter assemblages with different relative abundance of the component litters; we set up two types of litter assemblages that reflected the heterogeneity of bush cover in the inner maquis and at the edge maquis/gaps, as related to the leaf traits, i.e. sclerophylly vs mesophylly. We measured mass loss, decay of lignin, cellulose and ADSS (acid detergent soluble substances) and fungal mycelium ingrowth. The results show that over a 403-day incubation period, the decomposition of individual litters in mixtures deviated from that of monospecific litters and had different directions. In litter mixtures of the sclerophylls Phillyrea angustifolia and Pistacea lentiscus with the mesophyll Cistus, decomposition was lower than expected (antagonistic effect); in the mixtures of litters with similar physical structure (Ph. angustifolia and P. lentiscus with Quercus ilex) decomposition was faster than expected (synergistic effect). When considering the different decomposition phases, both negative and positive effects occurred in Quercus mixtures depending on the phase of decomposition. In both types of 3-species litter assemblages the greatest effect occurred in uneven mixtures rather than in even mixtures. Our results show that species composition drives the direction whilst the decomposability and the relative abundance drive the magnitude of non-additive effects of litter mixing on decomposition.